Individual physical activity, neighbourhood active living environment and mental illness hospitalisation among adults with cardiometabolic disease: a Canadian population-based cohort analysis - Neeru Gupta; Dan Lawson Crouse; Pablo Miah; Tim Takaro (BMJ Open, 2023)
Objectives This population-based observational study explores the associations between individual-level and neighbourhood-level indices of active living with inpatient mental healthcare use among adults with an underlying chronic cardiometabolic condition.Design and setting Data from the 2013–2014 Canadian Community Health Survey were linked longitudinally to hospital records from the 2013/2014‒2017/2018 Discharge Abstract Database and to a geocoded measure of active living environments (ALE). Relationships between individuals’ leisure-time physical activity and neighbourhood ALE with risk of hospital admission for mental health disorders were assessed using multivariable Cox regressions.Participants A national cohort was identified from the survey data of 24 960 respondents aged 35 years and above reporting having been diagnosed with diabetes, hypertension and/or heart disease.Outcome measure Potentially avoidable hospitalisation for a mood, anxiety or substance use disorder over a 5-year period.Results More than half (52%) of adults aged 35 years and above with a cardiometabolic disease were physically inactive in their daily lives, and one-third (34%) resided in the least activity-friendly neighbourhoods. The rate of being hospitalised at least once for a comorbid mental disorder averaged 8.1 (95% CI: 7.0 to 9.3) per 1000 person-years of exposure. Individuals who were at least moderately active were half as likely to be hospitalised for a comorbid mental health problem compared with those who were inactive (HR: 0.50 (95% CI: 0.38 to 0.65)). No statistically discernible associations between neighbourhood ALE and hospitalisation risks were found after controlling for individuals’ behaviours and characteristics, including in separate models stratified by age group and by sex.Conclusions The evidence base to support prioritisation of interventions focusing on the built environment favouring mental health-promoting physical activity among higher-risk adults at the population level, independently of individual-level behaviours and characteristics, remains limited.